The ratifications - Craig, P (Oxford University Press, 2020)
This chapter assesses the ratification of the Withdrawal Agreement by clarifying the means by which the UK and the EU gave effect to the exit treaty. It begins by looking at the ratification and legal implementation from the UK legal perspective. The UK is a dualist country as regards the relation between treaties and UK law. A treaty may therefore bind the UK at the international level, but will have no effect in UK domestic law unless and until it is ratified and incorporated into UK law via statute. The chapter sets out the foundational principles concerning dualism and explains the process through which the UK implemented the Withdrawal Agreement so as to satisfy the dualist precept. It also considers the interconnection between the EU Withdrawal Act 2018 and the EU Withdrawal Agreement Act 2020. The chapter then examines the ratification and its legal consequences from the EU perspective.